2002
DOI: 10.1016/s0375-9601(02)00015-4
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on universal quantum computer

Abstract: According to Deutsch, a universal quantum Turing machine (UQTM) is able to perform, in repeating a fixed unitary transformation on the total system, an arbitrary unitary transformation on an arbitrary data state, by including a program as another part of the input state. We note that if such a UQTM really exists, with the program state dependent on the data state, and if the prescribed halting scheme is indeed valid, then there would be no entanglement between the halt qubit and other qubits, as pointed out by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
(14 reference statements)
0
27
0
3
Order By: Relevance
“…Nishimura and Ozawa [13] compared various models of quantum computation. Various papers [14,15,16,17] have discussed how these models can halt coherently (all computation paths halting simultaneously) when two programs which halt at different times are used as input in superposition. [17] showed that it is undecidable whether a quantum Turing machine halts coherently for a general input.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nishimura and Ozawa [13] compared various models of quantum computation. Various papers [14,15,16,17] have discussed how these models can halt coherently (all computation paths halting simultaneously) when two programs which halt at different times are used as input in superposition. [17] showed that it is undecidable whether a quantum Turing machine halts coherently for a general input.…”
mentioning
confidence: 99%
“…States such as |ψ = 1 √ 2 (|0 + |10 ) are forbidden on the QTM but allowed on the SQTM. Second Quantized Halting Several papers [14,15,16,17] have pointed out issues in how quantum computations halt coherently (how all the computational paths halt simultaneously) on the quantum Turing machine [10,11] and Nielsen's parallel gate array [12]. The SQTM allows programs of different sizes to be input in superposition.…”
mentioning
confidence: 99%
“…Myers argued [4] that due to entanglement between a halt qubit and a system, it may be difficult to measure the halt qubit, which may spoil the computation. Subsequent discussions on the halting problem with a quantum computer have mainly focused on the superposition and entanglement of the halt qubit [5,6,7]. In this paper, we approach the halting scheme differently and use two pictures of quantum dynamics, i.e., the Schrödinger and Heisenberg pictures.…”
mentioning
confidence: 99%
“…[7], [8], [9], [10], [11]. We will not get too deep into this discussion, but rather analyze in detail the simple definition for halting by Bernstein and Vazirani [3], which we also use in this paper.…”
Section: A Quantum Turing Machines and Their Halting Conditionsmentioning
confidence: 99%